Analysis of Intraoperative Exposure to X-rays and Surgical Time in Different Techniques for Fixation of Transtrochanteric Fractures of the Femur - Guerra, Lucas Carneiro Curty Bastos; Chiarelli, Leo Ribeiro (Revista Brasileira de Ortopedia, 2021)
Objective The present study aimed to evaluate and compare the total surgical procedure time and intraoperative X-ray exposure during different techniques for fixation of transtrochanteric fractures of the femur in elderly patients, using extramedullary and intramedullary methods based on cephalic traction screws.Methods The Orthopedics and Traumatology Service from our hospital evaluated 107 patients with transtrochanteric fractures, including 34 males and 73 females, with age ranging from 61 to 101 years old. Fracture fixation was performed with a dynamic hip system (DHS) in 21 patients, a standard proximal femoral nail (PFN) in 55 subjects, and a standard gamma nail in 31 patients. All procedures were performed by the same surgeon and his team of nursing assistants, along with the same radiology technician using the same image intensifier. Total surgery time (in minutes) and X-ray emission (in centigrays [cGy]) were evaluated.Results Transtrochanteric fracture fixation with PFN provides a significantly shorter surgical time (p = 0.013) in comparison to the 2 other techniques. Intraoperative exposure to X-rays was significantly lower when using DHS (p = 0.015) as a fixation method when compared with gamma nail and PFN.Conclusion Although PFN resulted in the shortest surgical time, DHS was associated with the lowest X-ray exposure levels within the studied sample.
Keywords: cancer; femoral fractures; internal fixators; neoplasms, radiation-induced; X-rays